"I am spiritual, but not religious": Does one without the other protect against adolescent health-risk behaviour? - Malinakova, Klara; Kopcakova, Jaroslava; Madarasova Geckova, Andrea; van Dijk, Jitse P; Furstova, Jana; Kalman, Michal; Tavel, Peter; Reijneveld, Sijmen A (International journal of public health, 2019)
OBJECTIVES: Spirituality and religious attendance (RA) have been suggested to protect against adolescent health-risk behaviour (HRB). The aim of this study was to explore the interrelatedness of these two concepts in a secular environment. METHODS: A nationally representative sample (n = 4566, 14.4 ± 1.1 years, 48.8% boys) of adolescents participated in the 2014 Health Behaviour in School-aged Children cross-sectional study. RA, spirituality (modified version of the Spiritual Well-Being Scale), tobacco, alcohol, cannabis and drug use and the prevalence of sexual intercourse were measured. RESULTS: RA and spirituality were associated with a lower chance of weekly smoking, with odds ratios (OR) 0.57 [95% confidence interval (CI) 0.36-0.88] for RA and 0.88 (0.80-0.97) for spirituality. Higher spirituality was also associated with a lower risk of weekly drinking [OR (95% CI) 0.91 (0.83-0.995)]. The multiplicative interaction of RA and spirituality was associated with less risky behaviour for four of five explored HRB. RA was not a significant mediator for the association of spirituality with HRB. CONCLUSIONS: Our findings suggest that high spirituality only protects adolescents from HRB if combined with RA.
Keywords: riskování; Spirituality; Cross-Sectional Studies; spiritualita; Health-risk behaviour; Male; zdraví dospívajících; odds ratio; Adolescent; zdravotně rizikové chování; HBSC study; Adult; prevalence; Religion; dospělí; mužské pohlaví; Smoking; mladiství; Religious attendance; náboženství; Health Risk Behaviors; lidé; Risk-Taking; ženské pohlaví; Adolescence; Humans; Prevalence; průřezové studie; Adolescent Health; pití alkoholu; Alcohol Drinking; Odds Ratio; Female; kouření